Pengaruh Pengelolaan Dana Desa Terhadap Program Pemberdayaan Masyarakat Petani di Desa Bontula, Kecamatan Asparaga, Kabupaten Gorontalo - Karim, Israwati; Baruwadi, Mahludin H.; Machieu, Siti R Rahmatia (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
One of the government  initiatives o support commuity development and empowerment is thourgh the allocations of Village Funds. The allocations of Village Funds. The funds prioritize programs that empower farmers, thereby improving economic welfare in these villages. Bontula Village is one of the villages that has considerable potential in the field of agriculture, making it a strategic area for the empowerment of its farmers. The purpose of this study is to determine the effect of Village Fund Management on farmer empowerment programs. This study uses a quantitative descriptive approach, with farmersas the main participants. Based on the analysis conducted through Simple Lnear Regression and t-tests, it can be concluded that there is a significant relationship between Village Fund Management and the Farmer Empowerment Program in Bontula Village, Asparaga District, Gorontalo Regency. Furthemore, the findings show that Village Fund Management contributes 75,6% to the Farmer Empowerment Program, while the remaining 24,4% is determined by external factorsbeyond the scope of this study. The structural equantion is Y = 12,888 + 0,865 X. From the hypothesis analysis conducted, it was revealed that Village Fund Management has a positive impact significant impact on the farmer  Empowerment Program in Bontula Village, Asparaga Subdistrict, Gorontalo Regency. The utilization of Village Funds by prioritizing the empowerment of the farming community in Bontula Village is very strategic for improving the local economy. Example include programs such as providing facilities for plant nurseries and yield management. With good management of Village Funds, programs such as these can encourage increased productivity and welfare for farmers in Bontula Village.